Reduced Response of IRE1α/Xbp-1 Signaling Pathway to Bortezomib Contributes to Drug Resistance in Multiple Myeloma Cells. Issue 3 (May 2017) - Xu, Xiaoxuan; Liu, Junru; Huang, Beihui; Chen, Meilan; Yuan, Shiwen; Li, Xiaozhe; Li, Juan
Purpose: Proteasome inhibition with bortezomib eliminates multiple myeloma (MM) cells by partly disrupting unfolded protein response (UPR). However, the development of drug resistance limits its utility and resistance mechanism remains controversial. We aimed to investigate the role of IRE1α/Xbp-1 mediated branch of the UPR in bortezomib resistance. Methods: The expression level of Xbp-1s was measured in 4 MM cell lines and correlated with sensitivity to bortezomib. LP1 and MY5 cells with different Xbp-1s level were treated with bortezomib; then pivotal UPR regulators were compared by immunoblotting. RPMI 8226 cells were transfected with plasmid pEX4-Xbp-1s and exposed to bortezomib; then apoptosis was determined by immunoblotting and flow cytometry. Bortezomib-resistant myeloma cells JJN3.BR were developed and the effect on UPR signaling pathway was determined. Results: By analyzing 4 MM cell lines, we found little correlation between Xbp-1s basic level and bortezomib sensitivity. Bortezomib induced endoplasmic reticulum stress-initiated apoptosis via inhibiting IRE1α/Xbp-1 pathway regardless of Xbp-1s basic level. Exogenous Xbp-1s reduced cellular sensitivity to bortezomib, suggesting the change of Xbp-1s expression, not its basic level, is a potential marker of response to bortezomib in MM cells. Furthermore, sustained activation of IRE1α/Xbp-1 signaling pathway in JJN3.BR cells was identified. Conclusions: Our data indicate that reduced response of IRE1α/Xbp-1 signaling pathway to bortezomib may contribute to drug resistance in myeloma cells.